PERANCANGAN BRANDINGBOWELE SEBAGAI DESTINASI EKOWISATA KABUPATEN MALANG - Pranata, Hogi Er; Bahruddin, Muh; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract:The purpose of designing this Bowele branding is to make Bowele as an eco-tourism destination in the Malang districts. The study was conducted using qualitative research method is by conducting interviews, observation, documentation and literature to obtain the data used to support the manufacture of the design concept of branding. Data were analyzed with multiple stages of data reduction, data presentation and conclusion. From the analysis of the data found some keywords that refer to the branding communications strategy that will be used to reach the intended target audience. After analysis of the data, found a branding design concept or keyword of